Analysis of Obedience Factors of Distribution Facilities in Distributing Cosmetics in East Java - Pipin Eri Agustina, - (Universitas Aisyah Pringsewu (UAP) Lampung, 2022)
Cosmetics that have no marketing authorization number (MAN) can harm people's health. This study aimed to analyze the factors that affect the obedience of cosmetics distribution facilities in distributing cosmetics that have MAN in East Java based on Niven's theory (understanding the instructions, quality of interaction, beliefs, attitudes, personality, social isolation) and Milgram's theory (the status of the facilities, personal responsibility, the legitimacy of authority figures, the status of authority figures, peer support, the proximity of authority figures). This study was a cross-sectional study, using a validated questionnaire. 179 participants were chosen using simple random sampling. The data were analyzed using Partial Least Square (PLS) (α=0.05). The factor based on Niven's theory that has significant relationship with the obedience is the personality (p=0.001). The factors based on Milgram's theory that have significant relationship with obedience are the legitimacy of authority figures (p=0.025) and peer support (p=0.000). Whereas, understanding the instructions, quality of interaction, beliefs, attitudes, social isolation, status of facilities, personal responsibility, the status of authority figures, and the proximity of authority figures have no correlation. Milgram’s theory more affects obedience than Niven’s theory. Various kinds of education and monitoring evaluation of distribution facilities were implemented to improve obedience.